PENGARUH PEMBERIAN BEBERAPA JENIS PUPUK ORGANIK TERHADAP PERTUMBUHAN BIBIT KOPI ARABIKA (Coffea arabica L.) PADA MEDIUM SUBSOIL INSEPTISOL - Santi Maria; Wardati Wardati; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this research is to know Arabica coffee seedling (Coffea arabica L.) on medium subsoil Inseptisol. This research has been conducted in Experimental Garden of Agriculture Faculty of Riau University, Campus Bina Widya km 12,5 Simpang Baru Village, Tampan Sub District, Pekanbaru City. This study was conducted from March to July 2017. This study was conducted using a Complete Randomized Design (CRD). The treatments are several types of organic fertilizer consisting of six treatment namely K0: Without composting, K1: 50 g TKKS compost per polybag, K2: 50 g tofu waste compost per polybag, K3: 50 g coffee skin compost per polybag, K4: 50 g vermicompost per polybag, K5: 50 g kolarhino per polybag. Each treatment was performed three times in 18 experimental units. Data obtained from the observations were analyzed using variance analysis (Anova). Diversity results are followed by Duncan multiple range test at 5% level. The parameters used were the increase of seedling height, the increase of stem diameter, the increase of leaf number, total leaf area, root volume, seedling dry weight and shoot root ratio. The results showed that some kind of organic fertilizers both to the root volume of other parameters such as the increase of seedling height, the increase of stem diameter, the increase of leaf number, total leaf area, seedling dry weight and shoot root ratio. Provision of organic fertilizer vermicompost provide the best results than other organic fertilizer are TKKS, tofu waste, coffee skin and kolarhino.Keywords: Arabica coffee seedling, organic fertilizer, subsoil Inseptisol